Efficacy and safety of ultrasound-guided percutaneous microwave ablation for hepatocellular carcinoma at specific anatomic sites of the liver: a systematic review and meta-analysis - Zha, Jiandong; Zhang, Fang; Cao, Tuoyu; Li, Shasha; Shen, Xuelian; Xu, Liangliang; Chen, Wenqi (Frontiers in Surgery, 2025)
ObjectiveThis meta-analysis aims to assess the efficacy and safety of ultrasound-guided percutaneous microwave ablation (MWA) in the treatment of hepatocellular carcinoma (HCC) located at specific anatomic sites of the liver with those of non-specific sites.MethodsA systematic search was conducted across five databases, covering the period from the establishment of each database to September 30, 2024. Prospective and retrospective studies involving ultrasound-guided percutaneous MWA for the treatment of HCC were included. Data extraction and statistical analysis were performed using Stata 15.1 software. The main outcomes were 1-year, 3-year, and 5-year overall survival rates, complete ablation rates, and major complication rates. The results were presented as odds ratios (OR) with 95% confidence intervals (CI).ResultsA total of 9 studies were included, involving 2,381 patients, of which 1,047 had HCC at specific anatomic sites, and 1,334 had HCC at non-specific sites. The OR values (95% CI) for overall survival at 1 year, 3 years, and 5 years for patients with HCC at specific anatomic sites compared to non-specific sites were 0.89 (0.59, 1.35), 0.83 (0.66, 1.05), and 1.12 (0.91, 1.38), respectively. The OR for complete ablation rate was 0.97 (0.61, 1.53), and the OR for major complications was 1.44 (0.59, 3.51).ConclusionUltrasound-guided percutaneous MWA for HCC at specific anatomic sites shows similar efficacy and safety to that at non-specific sites, with no significant differences in survival rates, complete ablation rates, or complication rates.